2012
DOI: 10.1123/ijspp.7.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Status in Adolescent Judo Athletes Before and After Training in the Heat

Abstract: Adolescent judo athletes who train in tropical climates may be in a persistent state of dehydration because they frequently restrict fluids during daily training sessions to maintain or reduce their body weight and are not given enough opportunities to drink.Purpose:Determine the body hydration status of adolescent judo athletes before, immediately after, and 24 h after (24H) a training session and document sweat Na+ loss and symptoms of dehydration.Methods:Body mass and urine color and specific gravity (USG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 28 publications
0
37
2
Order By: Relevance
“…Nevertheless, the strength requirements and technical characteristics of different sports' practice may also be preventive factors for bone loss and bone-related injuries (Poutreau, Pelle, Collomp et al, 2006). Furthermore, it has been reported (Rivera- Brown & De Felix-Davila, 2012) that the fluid restriction practiced by many combat sport athletes when involved in weight loss processes (Artioli, Gualano, Francini et al, 2010), in conjunction with intense training in these sport in hot environments, resulted in serious dehydration, which might provoke heat-related injuries. Despite the described risks, most judo and wrestling athletes reduce their weight a short time before competition (Fabrini, Brito, Mendes et al, 2010;Brito, Castro Martins Roas, Souza Brito et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the strength requirements and technical characteristics of different sports' practice may also be preventive factors for bone loss and bone-related injuries (Poutreau, Pelle, Collomp et al, 2006). Furthermore, it has been reported (Rivera- Brown & De Felix-Davila, 2012) that the fluid restriction practiced by many combat sport athletes when involved in weight loss processes (Artioli, Gualano, Francini et al, 2010), in conjunction with intense training in these sport in hot environments, resulted in serious dehydration, which might provoke heat-related injuries. Despite the described risks, most judo and wrestling athletes reduce their weight a short time before competition (Fabrini, Brito, Mendes et al, 2010;Brito, Castro Martins Roas, Souza Brito et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recommendation of hydrating with 375-500 mL of water 30 minutes prior to the beginning of the training session, 12 of the 13 athletes were classified as hypohydrated, with other studies having also observed this initial state [3][4][5]. The intake of 250-300 mL of water at the beginning of an activity and the further intake of around 150 mL every 20 minutes during the exercise is known to be among the recommendations for ensuring hydration [9], however, the athletes taking part in our study showed themselves to be commencing training already in a worrying state of hypohydration.…”
Section: Discussionmentioning
confidence: 97%
“…RG and other sports (judo, football, futsal) demand high aerobic fitness, strength, balance, coordination, perception and cognition [3,4], skills that can be compromised when accompanied by a negative fluid deficit >2% [5]. Young athletes from different sports (rhythmic gymnastics, tennis, football, futsal, judo), frequently begin training sessions and competitions hypohydrated and are unable to recover from one training session to the next [3,[6][7][8][9], often using restricted fluid intake for the maintenance and loss of body weight [3,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations